Structural Convergence of the CEE Countries with the Euro Area: Evidence from the Distribution of Employment between the Economic Sectors - Stefanova, Kristina (UNWE Yearbook, 2021)
This paper examines the structural convergence of the CEE countries with the euro area with respect to the distribution of employment between the economic sectors. The existence of such a process contributes to the synchronization of business cycles and the efficiency of monetary policy. The purpose of the paper is to explore in which member states a convergence process with the euro area exists and smaller dissimilarities are observed over the period 2000 – 2018. Through the evaluation of the divergence index and the application of sigma convergence analysis it is identified that employment structure convergence of most CEE countries towards the euro area exists. However, considerably less dissimilarities with the euro area are observed over the whole period in countries that currently use the euro.